Positioning for success: building capacity in academic competencies for early-career researchers in sub-Saharan Africa. (2019) - Merritt, C.; Jack, H.; Mangezi, W.; Chibanda, D.; Abas, M.
Abstract : Background: Capacity building is essential in low- and middle-income countries (LMICs) to address the gap in skills to conduct and implement research. Capacity building must not only include scientific and technical knowledge, but also broader competencies, such as writing, disseminating research and achieving work–life balance. These skills are thought to promote long-term career success for researchers in high-income countries (HICs) but the availability of such training is limited in LMICs. Methods: This paper presents the contextualisation and implementation of the Academic Competencies Series (ACES). ACES is an early-career researcher development programme adapted from a UK university. Through consultation between HIC and LMIC partners, an innovative series of 10 workshops was designed covering themes of self-development, engagement and writing skills. ACES formed part of the African Mental Health Research Initiative (AMARI), a multi-national LMIC-led consortium to recruit, train, support and network early-career mental health researchers from four sub-Saharan African countries. Results: Of the 10 ACES modules, three were HIC-LMIC co-led, four led by HIC facilitators with LMIC training experience and three led by external consultants from HICs. Six workshops were delivered face to face and four by webinar. Course attendance was over 90% and the delivery cost was approximately US4500 per researcher trained. Challenges of adaptation, attendance and technical issues are described for the first round of workshops. Conclusions: This paper indicates that a skills development series for early-career researchers can be contextualised and implemented in LMIC settings, and is feasible for co-delivery with local partners at relatively low cost.